PERAN GURU AGAMA DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL DAN SPIRITUAL PADA ANAK SMA MUHAMMADIYAH 1 MEDAN - Intani, Yumi (Fakultas Agama Islam, 2020)
The low development of emotional and spiritual intelligence of students according to the opinion of the writer due to the lack of the role of religious teachers in instilling the values of education and teaching, especially in Islamic religious education to students, therefore in this research the writer wants to examine further the role of religious teachers in developing emotional intelligence and spiritual students through Islamic Religious Education, what are the efforts made by religious education teachers and what are the obstacles in developing students' emotional and spiritual intelligence. Based on the results of the study, the role of religious teachers shows the role of educators and teachers, as facilitators, motivators, managerial, as parents and as role models for students of Muhammadiyah 1 Medan High School in developing their emotional and spiritual intelligence. Emotional and spiritual intelligence of students of Muhammadiyah 1 Medan Senior High School showed the existence of good emotional and spiritual intelligence. Based on the research, the calculation of count ttable (3,837 2,021). Based on the determinant test of the calculation results it can be concluded that the emotional and spiritual intelligence of students increased influenced by variable X (the role of religious teachers) by 34.45%, the remaining 65.55% was influenced by other factors.